Improving work readiness through talent management, knowledge management and learning organizations in private universities - Ramaditya, Muhammad; Syahrul Effendi; Dwi Fitriani (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
This study aims to determine the work readiness of private universities students in LLDIKTI Region III. This study emphasizes on executiemphasisng talent management, knowledge management, career decision-making self-efficacy and learning organizations’ that can impact on is work readiness of universities student. The current high unemployment rate is not only caused by fewer available jobs, but it can also be caused by private higher education that not investing in enhancing their talent through independent program. The method used in this study is a survey method, where data is obtained from the results of collection using a questionnaire. The sample in this study were 397 respondents. The analysis tool used is PLS-SEM 3.0 version with the stratified random sampling method technique. The talent management can improve knowledge management, learning organization and work readiness. Besides, career development program also enhance preparation for work readiness Private university need to enhance the talent mapping, development and retention program for the academician to enhancing their work readiness. Such as development program from independence program in internship.